STUDI KOMPARATIF PERBEDAAN TOTAL PENJUALAN (OMSET) PEDAGANG BAKSO MENETAP DAN PEDAGANG BAKSO KELILING DI KOTA PEMATANGSIANTAR - HASTINA FEBRIATY; CEP DEDEN MUCHROJI (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Meatballs are a popular food in the community Traders meatballs is inseparable from economic development, then workers meatballs traders need serious treatment through an integrated development pattern. But in reality it until the pattern formation is still untouched, as expected. In this case, in addition to requiring substantial capital, business trade meatballs also requires a good ability of the owner to cultivate efforts made in order to obtain a large income. This research was conducted in Pematangsiantar by using primary data time series in 2014, which is derived from questionnaire data. Based on estimates, that the merchant has settled meatballs turnover or income very much different with meatballs itinerant traders.